The relationship between suicidal behaviors and atopic dermatitis in Korean adolescents. (October 2016) - Noh, Hye-Mi; Cho, Jung Jin; Park, Yong Soon; Kim, Jeong-Hyeon
Atopic dermatitis is a common skin disease in adolescents, which may have a negative effect on the mental and emotional health. We investigated the relationship between atopic dermatitis and suicidal behaviors in Korean adolescents. Participants included 74, 186 adolescents (38, 221 boys and 35, 965 girls) in middle and high school who completed the Eighth Korea Youth Risk Behavior Web-Based Survey. There were significant associations between atopic dermatitis and suicidal behaviors for girls. The overestimation of weight perception might have an additive impact on suicidal risk among girls. However, there were no significant associations between atopic dermatitis and suicidal behaviors in boys.